The relationship between upper anterior teeth colour and skin colour in both genders among Malaysians in USM Health Campus population - Moazam, Ryhana Mohammad Zakir Hiyat (2022)
Shade matching is the method used in dentistry to select artificial teeth colour. However, shade matching is not possible in some cases where the adjacent tooth is missing, discoloured, or unhealthy. Therefore, tooth colour shade selection according to adjacent facial features were suggested by previous studies to be used. One of these features was skin colour. The aim of this study was to find and model the relationship between tooth colour and skin colour in a way that can be used in dentistry. A convenience sampling was done to select 150 Malaysian staff and students of the Hospital Universiti Sains Malaysia, Health Campus, with equal sex distribution (75 males/ 75 females) to participate in this study. Digital photography was used to measure skin colour and maxillary central and lateral incisors’ colour by taking photos of participants’ faces and teeth in standardized settings. Photos were calibrated in Adobe Lightroom, and then colour measurement was done in Adobe Photoshop. Vita Easyshade spectrophotometer was also used to measure maxillary incisors’ colour. The form of colours was described in CIELab system. Microsoft Excel was used to develop the prototypes of Skin Shades Colour Chart, and Skin-Tooth Colour Chart by considering the colour differences ΔE as the controlling factor of colour classifications. The results of the t-test showed that there were significant differences in colour readings between Vita Easyshade Spectrophotometer and digital photography in all tests. The t-test also showed that spectrophotometer did not show any significant differences between males and females tooth colour. On the other hand, digital photography showed that females had lighter teeth than males in central incisors (p < 0.05) and in lateral incisors (p = 0.05) at significant level of 0.05. Three equations resulted from multiple regression analysis that described the direct relationship in digital camera’s readings between tooth colour (dependent variable), and skin colour, tooth type, and gender (independent variables) to predict tooth colour. Two prototypes of colour charts were developed in this study, Skin-Tooth colour chart that was driven from the Skin Shades Colour Chart. These two charts may be used as a guiding tool in clinics for selecting tooth colour by matching the charts with skin colour. By considering these results, tooth colour can be predicted by using the equations of this study, or by using the skin-tooth colour chart. Further studies should be done to investigate the skin-tooth colour chart variations in larger and diverse samples.